(CO)DESIGNING HOPE aqueous landscapes in transition. - Cipriani, Laura ([S.l.] : ROUTLEDGE, 2024)
Extreme weather events, droughts, floods, shifts in precipitation and temperature patterns, melting glaciers, sea-level rise, water salinization, and more generally, changes in the water cycle remind us that the climate crisis is mostly a water crisis. Perhaps even more serious is a crisis of imagination connected with thought and with creative, far-sighted action able to combine the visionary and the pragmatic. A response to these two crises can be provided by the disciplines of landscape architecture: these have always featured a plural, collective approach that comprises or originates from living systems and natural forces, on the involvement of human and nonhuman communities in the design process, and the inclusion of the time variable in future plans--without neglecting the necessary flexibility of creative and pragmatic thinking. How can landscape design and different forms of collaboration open new doors to face climate and water challenges? What hopes can spring from collective design in its broader meaning? This book sets out notions and ideas on water landscapes and (co)designed practices, identifying what hopeful routes might be taken for the three states of aqueous landscapes in transition--liquid, solid, and gas. The chapters show different scales and levels of design and collaborative practices: from large and governmental projects to small bottom-up interventions; from creative collaboration among designers to traditional community design; from participatory processes to nature as a co-designer for tackling the climate crisis. People, animals, plants, water, ice, fog, clouds, wind, sand, and rocks--all contribute to the cosmos' landscape symphony, and designing together can become a seed of hope to listen and embrace the Earth's climate changes.
Keywords: Water in landscape architecture; Climate change mitigation; Architects and engineers; Hydrologic cycle; Hydraulic engineering -- Environmental aspects; Principle (Philosophy); ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning